Research on the Current Situation and Countermeasures of Inpatient Cost and Medical Insurance Payment Method for Rehabilitation Services in City S - Tang, Dongfeng; Bian, Jinwei; He, Meihui; Yang, Ning; Zhang, Dan (Frontiers in Public Health, 2022)
Abstract Objective: This study aimed to introduce bed-day payment for rehabilitation services in City S, China, and analyze the cost of inpatient rehabilitation services. Key issues were defined and relevant countermeasures were discussed. Methods: Data on a total of 10,782 inpatient hospitalizations under long-term rehabilitation service contracts from 2015-2019 provided by the Health Security Bureau of City S Municipality were used to analyze the cost. Descriptive statistics, chi-square test, t-test, and multiple linear regression were used to explore the differences of cost in different groups and the influencing factors. Finally, 20 senior and middle management personnel of the hospitals were interviewed through a semi-structured interview method to further figure out the existing problems and countermeasures. Results: (1) During 2015-2019: Both discharges and the cost of rehabilitation hospitalization in City S rose rapidly. (2) The highest number of discharges was for circulatory system diseases (57.65%). Endocrine, nutritional, and metabolic diseases were noted to have the longest average length of stay (ALOS), reaching 105.8 days. Neurological, circulatory, urological, psychiatric, infectious, and parasitic diseases were observed to be generally more costly. (3) The cost of rehabilitation was determined to mainly consist of the rehabilitation fee (23.73%), comprehensive medical service fee (22.55%), and treatment fee (18.97%). (4) Besides the type of disease, age, nature of the hospital, and grade of the hospital, the most critical factor affecting the hospitalization cost was found to be the length of stay. (5) The key issues of City S's rehabilitative services system were identified to be the incomplete criteria, imperfections in the payment system, and the fragmentation of services. Conclusions: Patients have a huge demand for rehabilitation services. Payment according to bed day is the main payment method for rehabilitation services, but there is a conflict between rapidly rising cost and increasing demand for rehabilitation. Factors such as the length of stay and the grade of the hospital influencing the cost were defined. Lack of criteria, imperfections in the payment system, and the fragmentation of services limit sustainability. The core approach is to establish a three-tier rehabilitative network and a perfect modern payment system.